THE DESIGN MODEL OF INTENSIVE VANAME SHRIMP PONDS FOR ECO-GREEN AQUACULTURE DEVELOPMENT IN THE AREA OF PROBOLINGGO, EAST JAVA, INDONESIA - Jadfan Sidqi Fidari; Maftuch Maftuch; Andi Kurniawan; Mohammad Bisri (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
Probolinggo, East Java, Indonesia, is an area with a high potential for shrimp aquaculture because these areas meet the criteria for candidate vaname shrimp aquaculture. Probolinggo in tropical regions with stable climate dan sea waves that have the potential for vaname shrimp aquaculture. The analysis required the following data: tidal data, topographic maps, network layouts, and water quality data for shrimp. This research was conducted by using the facilities at the brackish water and Marine Fisheries Laboratory of Probolinggo; an eco-green aquaculture circulation system was modeled and assessed using shrimp pond. First, the survey was located in Probolinggo City area, with coordinates 7° 44? 30.03? S and 113° 13? 58.68?. The methods used hydrological analysis: Water needs analysis for aquaculture irrigation based on the rules given by the Food and Agriculture Organization and water circulation analysis (Feedpedia, 2016). Material strength analysis of the embankments of the model pools: The comparison of area ratio toward embankment type dimension, design of dike and ponds, water filling discharge of brackish-water pond, and stages for ponds model design development. The results of the research suggested that dike should be planned to be as high as 1.5 m at the highest tide. The results of observations and tables of tidal recordings that had been verified then became the primary benchmark for planning the shrimp pond bottom. Based on the results of the analysis, it was found that the tidal height in the study location areas ranged from 2.5 to 3 m. A total of 80% of the area was used for production ponds.